2012
DOI: 10.1063/1.4764004
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial reaction-dominated full oxidation of 5 nm diameter silicon nanowires

Abstract: Silver catalyzed ultrathin silicon nanowires grown by low-temperature chemical-vapor-deposition J. Appl. Phys. 107, 096105 (2010); 10.1063/1.3393601Study of the effect of gas pressure and catalyst droplets number density on silicon nanowires growth, tapering, and gold coverage While almost all Si nanostructures, including Si nanowires (SiNWs), Si nanocrystals, and Si nanotrench-like structures on a supra-or sub-10 nm scale exhibit self-limiting oxidative behavior, herein we report full oxidation of SiNWs 5 nm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Consequently, the thinner Si-NWs will be readily oxidized under the same driving force of oxidation, leading to full oxidation, as observed in the sub-10 nm Si-NWs. [10][11][12]14 In summary, the present MD simulation showed that the residual stress decreased with increasing curvature in the sub-10 nm regime of the diameter. In this regime, the unoxidized Si core of the thinner Si-NWs deformed more to compensate for the volume expansion of the surface oxide layer, resulting in the smaller compressive stress.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Consequently, the thinner Si-NWs will be readily oxidized under the same driving force of oxidation, leading to full oxidation, as observed in the sub-10 nm Si-NWs. [10][11][12]14 In summary, the present MD simulation showed that the residual stress decreased with increasing curvature in the sub-10 nm regime of the diameter. In this regime, the unoxidized Si core of the thinner Si-NWs deformed more to compensate for the volume expansion of the surface oxide layer, resulting in the smaller compressive stress.…”
supporting
confidence: 53%
“…[2][3][4][5][6][7][8][9][10][11][12][13] However, recent experimental work with Si-NWs with diameters of approximately 10 nm reported full oxidation of the NWs. [10][11][12][13][14] These experimental observations are puzzling from the viewpoint of the previous theoretical model that the self-limiting oxidation is caused by the interfacial compressive stress which is proportional to the curvature of NWs. [7][8][9] The theoretical analysis would imply that the oxidation is extremely limited or totally suppressed in very thin Si-NWs.…”
mentioning
confidence: 90%